Bistable (Supra)molecular Switches on 3D-Printed Responsive Interfaces with Electrical Readout - Muñoz, Jose; Redondo, Edurne; Pumera, Martin (ACS applied materials & interfaces, 2021)
Molecular switching memories have gained great importance in recent years because of the current sharp increase in the production of consumer electronics. Herein, 3D-printed nanocomposite carbon electrodes (3D-nCEs) have been explored as unconventional responsive interfaces to electrically readout bistable molecular switches via electrochemical impedance spectroscopy as the output system. As a proof-of-concept, two different 3D-printed responsive interfaces have been devised using surface engineering for covalently anchoring (supra)molecular components that well-define two electrical states (on/off) driven by either electrical or optical stimuli. Accordingly, this work paves the way for the functionalization of 3D-nCEs through fundamental chemistry, opening up new horizons in unprecedented tailored 3D-printed responsive interfaces which could be utilized as potential (bio)sensors, (opto)electronic devices, or molecular logic gates.
Keywords: electrochemical impedance spectroscopy; supramolecular chemistry; molecular logic gates; 3D printing; optoelectronics; 3D-printed electrodes; graphene/PLA